Imbalance in T Follicular Helper Cells Producing IL-17 Promotes Pro-inflammatory Responses in MuSK Antibody Positive Myasthenia Gravis - Li, Yingkai (J Neuroimmunol, 2020)
A detailed understanding of the role of Tfh cells in MuSK-antibody positive myasthenia gravis (MuSK-MG) is lacking. We characterized phenotype and function of Tfh cells in MuSK-MG patients and controls. We found similar overall Tfh and follicular regulatory (Tfr) T cell frequencies in MuSK-MG and healthy controls, but MuSK-MG patients exhibited higher frequencies of Tfh17 cells and a higher ratio of Tfh:Tfr cells. These results suggest imbalanced Tfh cell regulation, further supported by increased frequencies of CD4 T cells co-producing IL-21/IL-17 and IL-17/IFN-γ, and increased Tfh-supported IgG production. These results support a role for Tfh cell dysregulation in MuSK-MG immunopathology.